The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0nr02953j
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the NIR-triggered chemotherapy therapeutic window of magnetic and thermoresponsive nanogels

Abstract: The combination of magnetic nanoparticles and thermoresponsive nanogels represents an appealing strategy for the development of theranostic probes. These hybrid nanocarriers present several advantages such as outstanding properties for guided...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
(89 reference statements)
2
7
0
Order By: Relevance
“…Since the resulting nanogels showed good biocompatibility, the concept was expanded in a second study by using magnetic nanoparticles as crosslinkers (Figure 11). 145 In this case, the same tendency was observed for tuning the VPTT by the ratio between DEGMA and OEGMA. Due to the magnetic properties of the colloids, they show great potential for guided therapy applications, photothermal release, and magnetic resonance imaging.…”
Section: Precipitation Polymerizationsupporting
confidence: 67%
“…Since the resulting nanogels showed good biocompatibility, the concept was expanded in a second study by using magnetic nanoparticles as crosslinkers (Figure 11). 145 In this case, the same tendency was observed for tuning the VPTT by the ratio between DEGMA and OEGMA. Due to the magnetic properties of the colloids, they show great potential for guided therapy applications, photothermal release, and magnetic resonance imaging.…”
Section: Precipitation Polymerizationsupporting
confidence: 67%
“…The photothermal conversion efficiency (PTCE) was calculated using the heating profiles of MPNC1, MPNC2, AgMNCs, and MNCs (all samples in a concentration of 0.125 mg/mL; Figure d–e). Notably, for these experiments, we had decided to use a 785 nm fix wavelength laser despite not being in the absorption maxima of the MPNCs for several reasons: (a) it is a more bioapplicable wavelength since it is better fitting in the biological NIR window, (b) it is extensively used for both gold- and iron-based nanoparticles and therefore gives us a better comparison, and (c) it is the closest wavelength to the NIR window where we can observe a contribution from the silver, gold, and anisotropic gold nanoparticles in the UV absorption (Figure c). As predicted by the UV–vis spectrum traces, AgMNCs significantly improved the PTCE of the MNCs from 18 to 27.9% due to the contribution of the silver atoms to the plasmonic band.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ultrasonication-assisted free radical precipitation/dispersion polymerization was employed as the synthetic procedure. As indicated in a previous work, in the presence of inorganic NPs, the ultrasonication strategy should guarantee their colloidal stability during polymerization [ 42 ]. Therefore, inorganic cores are expected to be homogeneously distributed inside the polymeric network, avoiding particle aggregation, and maximizing the available surface for the polymeric covering.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies performed with PNGs and magnetic NGs, demonstrated that the molar ratio of OEG monomers: DEGMA:OEGMA 80:20 allows to obtain appropriate LSCT for biomedical applications [ 31 , 34 , 42 ]. Therefore, in the present work, this condition was explored with the inorganic MSNs.…”
Section: Resultsmentioning
confidence: 99%